Tranformation of Islamic Capital Market ih the Digital Era: Analysis of the Role of Financial Technology in Increasing Participation of Young Investors - Gifari, Nur Rahmat; Warnila, Warnila; Gaffar, Dian Anugrah (Phinisi Applied Accounting Journal, 2025)
This study aims to comprehensively examine the role of financial technology (fintech) in enhancing youth participation in Indonesia’s Islamic capital market. Employing a descriptive qualitative approach, data were collected through literature review from academic journals, regulatory reports, and industry publications, and analyzed using content analysis techniques. The findings reveal that fintech significantly contributes to expanding youth investor engagement through three main mechanisms: lowering barriers to entry, integrating educational content within investment platforms, and personalizing services aligned with the preferences of younger generations. The study proposes four strategic approaches to strengthen this development, namely integrative digital-based financial literacy programs, enhancement of user experience design, cross-sector collaboration within the Islamic capital market ecosystem, and sustainable product innovation. The novelty of this research lies in the development of a digital transformation model for the Islamic capital market, consisting of four key dimensions—access, product, interaction, and education—which provides a comprehensive framework that has been largely overlooked in previous literature Keywords:, Islamic fintech, youth investors, Islamic capital market, digital transformation, financial inclusion Penelitian ini bertujuan untuk mengkaji secara mendalam peran teknologi finansial (fintech) dalam mendorong peningkatan partisipasi investor muda di pasar modal syariah Indonesia. Dengan menggunakan pendekatan deskriptif kualitatif, data dikumpulkan melalui studi kepustakaan yang bersumber dari jurnal ilmiah, laporan regulator, serta publikasi industri terkait, dan dianalisis menggunakan teknik analisis isi. Hasil temuan menunjukkan bahwa fintech memiliki kontribusi signifikan dalam membuka akses yang lebih luas bagi investor muda melalui tiga mekanisme utama, yaitu penurunan hambatan awal investasi (barrier to entry), integrasi edukasi ke dalam platform investasi, serta personalisasi layanan yang selaras dengan preferensi generasi muda. Penelitian ini juga mengusulkan empat pendekatan strategis yang dapat diadopsi oleh pemangku kebijakan dan pelaku industri, yakni pengembangan edukasi integratif berbasis digital, peningkatan kualitas pengalaman pengguna (user experience), penguatan kolaborasi antar pihak dalam ekosistem pasar modal syariah, serta inovasi produk yang berkelanjutan. Kebaruan dari penelitian ini terletak pada pemodelan transformasi digital pasar modal syariah yang mencakup empat dimensi utama, yaitu transformasi akses, produk, interaksi, dan edukasi sebuah pendekatan yang belum banyak diangkat secara menyeluruh dalam penelitian sebelumnya Keywords :, fintech syariah, investor muda, pasar modal syariah, transformasi digital, inklusi keuangan